UNIMAS nursing students' experiences during Clinical attachment in Sarawak General Hospital (SGH), Kuching - Law, Agnes Siew Yen (Universiti Malaysia Sarawak, 2012)
The purpose of this qualitative research was to explore the experiences of UNIMAS nursing students during clinical attachment in Sarawak General Hospital (SGH), Kuching. Purposive sampling was used and semi-structured interviews with open-ended questions were held with ten nursing students who wee in their third and final year of the Bachelor of Nursing with Honours Pragramme.